SCIENTIFIC RESEARCH OF ENERGY-SAVING TECHNOLOGY OF COAL PROCESSING AND SEPARATION OF METALS FROM COAL (Scientific journal of the Fergana State University, 2024)
This paper presents the scientific background of a pilot plant for beneficiation of coal and the research of an energy-efficient technology for the separation of metals from coal. In addition, the scientific results of the analysis of the results of the enrichment of different brands of lignite with the help of a pilot device are presented. The main parameters of 2BR-B2 and 2BOMSSh-B2 lignites before and after enrichment are presented. In order to obtain high-quality coal products, it is necessary to develop a technology of coal enrichment in a complex way. For this, a new flotation reagent is developed, its physico-chemical properties, efficiency in flotation enrichment, and coal gas extraction technology require development. An electron microscope image of 2BR-B2 Angren lignite before enrichment and information on its elemental composition and scientific analysis are presented. Preliminary scientific results were obtained for this and presented in this article.